Phytochemicals constituent and antioxidant activities in Musa x paradisiaca flower - Mahmood, Azizah; Ngah, Nurziana; Omar, Muhammad Nor (EuroJournals Publishing, Inc., 2011)
The objective of this study is to find out qualitatively and quantitatively phytochemical constituents and antioxidant activities in the flower of Musa x paradisiaca extracts. The extracts from various solvents; petroleum ether, chloroform, ethanol and water were investigated for the presence of alkaloid, saponin, glycoside, tannin, flavanoid, terpenoid and steroid. Particular reagents were used to screen phytochemicals in the samples and their presence was indicated by the changes of colour, precipitation or turbidity. Phytochemicals studies on banana flower extracts showed the presence of alkaloids, glycosides, steroids, saponins, tannins, flavanoids and terpenoids. Quantitative analysis by gravimetric method showed that the flower of M. x paradisiaca contains 1.56 ± 0.2 g/100g alkaloid and 1.43 ± 0.14 g/100g saponin. In spectrometric method, the flower also contains 5.83 ± 0.78 g/100g total phenolic, 88.31 ± 4.53 mg/100g tannin and 3.98 ± 0.01 mg/100g flavanoid. DPPH (1, 1-diphenyl-2-picrylhydrazyl) free radical scavenging assay of ethanol extract demonstrated stronger antioxidant activity than aqueous extract in which the IC50 value were 1.01 ± 0.16 mg/ml and 1.52 ± 0.13 mg/ml, respectively.